STUDENTS’ PERCEPTION ON THE APPLICATION OF TIMED WRITING PRACTICE (TWP) - Muh Syafei (Universitas Muria Kudus, 2019)
Abstract This preliminary research is as a part of learning need analysis for developing a discourse based writing material with a timed-writing technique in an English teacher education department in Indonesia. In timed writing practice (TWP), students must write a paragraph on a sheet of paper without help in a given time limit. However, no empirical information on whether the students agree or disagree with the application of timed writing and the reasons behind their perceptions is not yet avaiable.The research subjects consist of 31 students who take writing course. The objectives are to investigate (1) the extent of the students’ acceptance and (2) the reasons behind the acceptance on the application of timed-writing practice (TWP) in writing class. A qualitative analysis is administered by identifying and classifying contents of students’ opinions and reflections expressed in the students’ responses to questionare. Twenty five students (81%) agree with the application of TW. Four students (13%) disagree and 2 students (6%) give no preference. Timed writing are perceived as (1) Encouraging Writing Activity, (2) Improving Time Management and Control, (3) Training Thinking Skills, (4) Improving Writing Skills, (5)Training Speed Writing, (6) Improving Soft Skills, (7) Giving Challenging Activity, and (8) Improving Concentration and Accuracy. The reasons from those who disagree are: (1) Feeling nervous and confused (2) Having insufficient preparation time, and (3) Expecting Variation of Activity. In conclusion, timed writing is mostly accepted and positively perceived by the students with very high category. Reasons from those who disagree must also be taken into consideration for future betterment. Based on the research findings, the timed writing, accordingly, can be used as a technique or a strategy to be integrated in a discourse-based writing material for students of English teacher education program.Key Words: Timed-Writing, Students’ Acceptance, Reasons